Sp-Hybridized nitrogen doped graphdiyne for high-performance Zn–air batteries. (5th October 2021) - Zhao, Yasong; Wan, Jiawei; Yang, Nailiang; Yu, Ranbo; Wang, Dan
Abstract : The sp-hybridized nitrogen atoms (sp-N) have been site-specifically doped into graphdiyne (GDY). The precisely constructed sp-N doped GDY displays superior electrocatalytic activity for Zn–air batteries. Abstract : Zn–air batteries have drawn extensive attention owing to their high specific energy, light weight, convenient operation, and environmental friendliness. However, their practical application remains a challenge due to unsatisfactory performance and high-cost. Engineering highly efficient electrocatalysts, especially metal-free ones, for Zn–air batteries is crucially important. Doping heteroatoms can provide more active sites by the modification of electron distribution, and thus the rational design of the doping form and amount is an effective approach for performance enhancement. Herein, the unique sp-hybridized nitrogen atoms (sp-N) are site-specifically doped into graphdiyne (GDY) at a higher amount and with good selectivity. The precisely constructed sp-N doped GDY displays superior electrocatalytic activity and durability, which make it a distinctive air cathode for Zn–air batteries. Importantly, as an air cathode, sp-N doped GDY displays outstanding performance and robust stability, affording a peak power density of 195.7 mW cm −2, exceeding that of the commercial Pt/C catalyst (180.3 mW cm −2 ), and prominent stability. This work provides an extraordinary route for advancing metal–air cathode materials.